2017
DOI: 10.1080/01612840.2017.1335362
|View full text |Cite
|
Sign up to set email alerts
|

General Beliefs and Stigma Regarding Illicit Drug Use: Perspectives of Family Members and Significant Others of Drug Users in an Inner City in Brazil

Abstract: People who use drugs are continuously subjected to harsh stigmatization through a process of relational and social degradation, which limits their possibility for recovery. This quantitative study explores the perspectives of family members or significant others of illicit drug users, regarding general beliefs about illicit drug use and their stigma. Respondents agree that most people do not trust people who use drugs, disregard individuals who have been hospitalized due to drug problems and do not think peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
3
0
2
Order By: Relevance
“…Accordingly, harm reduction interventions based on peer support have a key role in building a therapeutic alliance with people who use drugs [ 54 , 55 ], promoting treatment engagement [ 56 58 ], and providing quality care for minority groups [ 59 , 60 ], as harm reduction workers have lived experiences similar to the service users and high levels of empathy. This approach is fundamental since [ 61 ] people who use AOD experience a high level of stigma [ 62 , 63 ] and, as a result, have lower access to treatment in low- and middle-income countries [ 50 , 54 , 57 , 64 ]. A study conducted in 20 countries showed that people from countries with prohibitionist drug policies had lower help-seeking rates compared to countries with relatively liberal drug policy regimes [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, harm reduction interventions based on peer support have a key role in building a therapeutic alliance with people who use drugs [ 54 , 55 ], promoting treatment engagement [ 56 58 ], and providing quality care for minority groups [ 59 , 60 ], as harm reduction workers have lived experiences similar to the service users and high levels of empathy. This approach is fundamental since [ 61 ] people who use AOD experience a high level of stigma [ 62 , 63 ] and, as a result, have lower access to treatment in low- and middle-income countries [ 50 , 54 , 57 , 64 ]. A study conducted in 20 countries showed that people from countries with prohibitionist drug policies had lower help-seeking rates compared to countries with relatively liberal drug policy regimes [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…O preconceito e o estigma referente aos usuários, e aos seus familiares, acentuam a vulnerabilidade das pessoas. Nessa perspectiva, são as populações empobrecidas que vivenciam mais intensamente os problema associados ao contexto de consumo das drogas, como a violência e o tráfico (17) . A assistência social precária e a dificuldade no acesso aos serviços públicos favorecem a ruptura dos laços entre as pessoas e a sociedade.…”
Section: Discussionunclassified
“…Caracterizado pelo processo acumulativo e multidimensional que separa e inferioriza as pessoas, os grupos, as comunidades e os territórios (4,12,15) . A exclusão social coexiste em vários tipos de fenômenos sociais, tais como o desemprego, a marginalidade, o preconceito e o pauperismo (17)(18) .…”
Section: Discussionunclassified
“…[4][5][6][7] For the wives of drug addicts, mental health is a major issue. [8][9][10][11][12][13][14][15][16] Wives of drug addicts also often have problems with their social networks, like not being able to get help from others and not being able to keep in touch with family and friends, 10,13,[16][17][18] experiencing violence and persecution, 10,12,17,[19][20][21] experiencing issues related to marital conflict 8, 10,18,22 and experiencing economic strain. 12,[14][15][16][17][22][23][24][25] It is predicted that the wives of drug users will have a negative impact on their overall wellbeing as a result of having to deal with a large number of negative situations.…”
Section: Introductionmentioning
confidence: 99%